EFFICACY OF PLASTIC MULCHING, MARIGOLD INTERCROPPING AND FUNGICIDAL SPRAY AGAINST EARLY BLIGHT OF TOMATO CAUSED BY ALTERNARIA SOLANI - P. P. JAMBHULKAR; M. L. MEGHWAL; R. K. KALYAN (The Bioscan, 2012)
Early blight of tomato caused and disseminate by conidial spores of Alternaria solani. Conidial spores of A. solani are seed, soil and air borne therefore any single method of disease management will not control the disease thus in this study a consortia of plastic mulching, marigold intercropping and spray with fungicides like propineb, aureofungin and azoxystrobin have been evaluated to reduce disease severity.Treatments having plastic mulching and marigold intercropping found to hinders the conidial movement than the non mulched and non intercropped. Treatment with consortia of plastic mulching, marigold intercropping and 3 sprays with azxoystrobin 23% SC hinders conidial movement to the maximum extent and reduced disease severity by 52-55% and only 2.0-2.1% fruit losses were recorded which ultimately fetch maximum fruit yield of 31.5- 33.4 t/ha yield respectively in both the experimental years. At the end of the evaluation period (9 WAT), the reductions in conidial density due to consortium treatment of plastic mulching, marigold intercropping and spray of azoxystrobin 23% SC were 25.8- 26.2% and 24.7-25.7% for the consortium treatment of plastic mulching, marigold intercropping and spray of Propineb 70WP, in both the years.